The Culinary Competitive Resources Model Explores The Mediating Role Of The Relationship Between Market Orientation And Sales Performance In The Traditional Culinary Industry In Central Java, Indonesia - Andi Setiawan; Sugiyanta Sugiyanta; Bagus Yunianto Wibowo; Rif’ah Dwi Astuti; Sri Wahyuni (Cita konsultindo, 2024)
The culinary industry in Indonesia experienced growth in 2022 after experiencing the impact of the COVID-19 pandemic. The same thing happened to the culinary industry in Central Java. The concept of